2018
DOI: 10.1017/dmp.2017.135
|View full text |Cite
|
Sign up to set email alerts
|

Something in the Water: Hospital Responds to Water Crisis

Abstract: Early on August 2, 2014, in the city of Toledo, Ohio, a media alert informed the public that traces of microcystin, a hazardous toxin, had been detected in the drinking water. The warning stated that residents should not drink, boil, or even touch the contaminated water. A water crisis of this magnitude was recognized to pose a potentially serious and significant impact on patient care and safety in health care environments. ProMedica Toledo Hospital's Emergency Operation Plan addressed 3 critical issues: safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 4 publications
0
22
0
1
Order By: Relevance
“…Multiple studies also identified patients as important actors to involve in the emergency preparedness phase ( 28 , 37 , 40 , 43 ). To a lesser extent, other health care facilities which are not affected by the outage or impairment, the community in which the hospital structure is located, and social networks are also mentioned as essential to enhance networking responsiveness and communication plans ( 23 , 37 , 41 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies also identified patients as important actors to involve in the emergency preparedness phase ( 28 , 37 , 40 , 43 ). To a lesser extent, other health care facilities which are not affected by the outage or impairment, the community in which the hospital structure is located, and social networks are also mentioned as essential to enhance networking responsiveness and communication plans ( 23 , 37 , 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the type of emergency, e.g., earthquakes, or chemical spills, the most common and first hospital response was the provision of drinking water using bottled of water ( 17 , 21 , 22 , 27 , 31 , 41 ). All studies, except one conducted in Sri Lanka, reported on disasters that happened in the United States.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Redfern a kolektiv se ve svém článku zaměřují hlavně na oblast externích dodavatelů, kteří hrají v krizovém plánování klíčovou roli pro zvládání mimořádných událostí nebo krizových situací. Autoři také v diskuzi vyzývají ostatní zdravotnická zařízení, aby se při sestavování vlastních havarijních plánů zaměřila na případ dlouhodobé mimořádné události s postihem velkého území (17).…”
Section: Přehledové Práceunclassified
“…Potential damage to the system can lead to the unavailability of drinking water. For example, a contamination led to disruptions in Toledo (Redfern et al 2018) and Flint (Ruckart et al 2019). Moreover, the system can be affected by natural disasters.…”
Section: Motivationmentioning
confidence: 99%